Machado de Lima, N.M. & Branco, L.H.Z. (2020) Biological soil crusts: new genera and species of Cyanobacteria from Brazilian semi-arid regions. Phytotaxa 470 (4): 263–281. - Machado De Lima, Náthali Maria; Branco, Luis H.z. (Phytotaxa, 2020)
N/A